Survey of disbudding practice on Czech dairy farms - Staněk, S; Šárová, R; Nejedlá, E; Šlosárková, S; Doležal, O (Journal of dairy science, 2018)
Disbudding is a routine practice in many dairy herds due to the effort to decrease the risk of injuries. Although the disbudding practice is regulated, it can vary among farms. The variation may be caused by many factors, such as herd size or type of breed, but also by farmers' perception of pain caused by disbudding. Hence, the aim of this study was to specify the disbudding practice on dairy farms in the Czech Republic and to assess these practices, including the use of pain mitigation medication, by breed, herd size, and sex of the disbudded calves. We analyzed data from 106 Czech dairy farms, which were collected by a trained interviewer at dairy meetings in 2014-2015. The farmers answered questions regarding the farm's basic characteristics, disbudding practice, and his/her attitude to the pain caused by disbudding. To test the influence of breed, herd size, and sex of disbudded calves on different variables, logistic regression models were used. Disbudding was performed in 92.5% of the surveyed farms; 63.3% of dairy calves were disbudded before 4 wk of age, and Czech Fleckvieh calves were 2.8 times more likely to be disbudded before 4 wk of age than Holstein calves. The hot-iron method was the most used method (69.4%). Calves were 4.5 times more likely to be disbudded by hot iron in herds where both heifers and bulls were disbudded than in herds where only heifers were disbudded. Most (>90%) surveyed farms did not use any pre- or post-procedure medication to mitigate the pain caused by disbudding. The disbudding procedure was performed mainly by farm personnel (94.9%), who were trained by a veterinarian or veterinary technician (46.9%) or by other farm personnel (37.8%) or were not trained (15.3%). Two-thirds of farmers observed behavioral changes in calves after disbudding. Most farmers estimated the pain caused by disbudding to be mild or moderate (20.4 or 45.9%, respectively) and 15.3% of farmers estimated it to be severe. Almost a quarter of interviewed farmers were unable to assess the duration of pain, 39.8% farmers estimated that the pain lasts only several minutes, and 20.4% estimated that the pain lasts up to 6 h. We detected a tendency that farmers of larger herds estimated pain duration to be shorter (odds ratio = 1.2). To improve calves' welfare, training is needed in disbudding practice, focusing on the advantage of pain mitigation.
Keywords: bolest; Horns; Pain; Surveys and Questionnaires; Humans; farm management; pracovní síly; chov zvířat; Female; mladý dospělý; dospělí; Attitude; zemědělci; lidé; Farmers; zvířata; disbudding; rohy; průzkumy a dotazníky; Adult; Cattle; ženské pohlaví; welfare; Male; skot; Czech Republic; Workforce; Farms; veterináři; Young Adult; Animal Husbandry; postoj; Animals; calf; Česká republika; mužské pohlaví; Veterinarians; farmy